MODIFIKASI BOLA KARET UNTUK MENINGKATKAN MINAT PADA MATERI BOLA VOLI SISWA KELAS V SD - Deka Ismi Mori Saputra; Rina Mariana (Jurnal Muara Pendidikan, 2022)
This research is motivated by the students' interest in volleyball game is still very low, this is because many students complain about the use of hard balls, so in this case the author tries to modify the ball to be lighter and not sick when used, with the hope that it can increase student interest 88 / VI Elementary School Bangko V Merangin Regency in a volleyball game. The study used a Class Action Research design which was carried out in two cycles, each cycle consisting of planning, implementing actions, observing and reflecting. The subjects of this study were students of class V of elementary school 88 / VI Bangko V, totaling 21 students. Volleyball learning outcomes data obtained through performance tests, observation sheets are used to collect data on student activities in following the volleyball learning process by learning to use a rubber ball.The results of this study were obtained based on an assessment of the interests of Grade V students of 88 / VI Elementary School Bangko. From the aspect of the assessment the percentage of completeness of grade V students of 88 / VI Elementary School Bangko V Merangin Regency cycle I was 47.62%. The results of the assessment of aspects of volleyball learning in the first cycle showed students achieving the KKM criteria or values> 75. There was a significant improvement from the condition of cycle I to cycle II. Volleyball learning assessment results obtained from the first cycle were as many as 14 students who completed. Whereas in the second cycle stage, the percentage of completeness of the total value of volleyball learning interest in grade V elementary school students 88 / VI Bangko V Merangin Regency is 85.71%, in other words> 75 or has met the KKM. Of the 21 students, 18 are stated to have reached KKM or only 3 have completed KKM. Based on the results of the study it was concluded that volleyball learning through modification of rubber balls can improve student learning outcomes of Class V elementary schools 88 / VI Bangko V. For Physical Education teachers in Primary Schools can apply learning effectively according to Physical Education lessons especially in ball learning volleyball.